Socioeconomic determinants and inequalities in exclusive breastfeeding among children in Peru - Hernández-Vásquez, Akram; Vargas-Fernández, Rodrigo (Frontiers in Nutrition, 2022)
To examine the socioeconomic determinants and perform a decomposition analysis of socioeconomic inequalities in exclusive breastfeeding (EBF) in Peruvian children 6 to 59 months of age. Cross-sectional study using the 2021 Demographic and Family Health Survey. The dependent variable for the study was EBF up to 6 months of age. Poisson log generalized linear regression models were fitted to evaluate the association between EBF and the independent variables, and concentration curves and Erreygers concentration index decomposition were used to analyze inequalities in EBF. A total of 9926 surveyed participants were included. The prevalence of EBF was 70.5%. Women who were married, self-identified as native, received EBF training, resided in the highlands and jungle, and their child was the second or older showed a higher likelihood of EBF. EBF was concentrated among the poorest mothers and the major contributors were residing in the highlands and jungle and belonging to the middle and wealthy quintiles. EBF is concentrated among the poorest women, creating a persistent gap between the poor and the rich. Greater efforts are needed to promote EBF in all children regardless of socioeconomic status.